Clickable polysaccharides for biomedical applications: A comprehensive review. (October 2022) - Khodadadi Yazdi, Mohsen; Sajadi, S. Mohammad; Seidi, Farzad; Rabiee, Navid; Fatahi, Yousef; Rabiee, Mohammad; Dominic, C.D. Midhun; Zarrintaj, Payam; Formela, Krzysztof; Saeb, Mohammad Reza; Bencherif, Sidi A.
Abstract: Recent advances in materials science and engineering highlight the importance of designing sophisticated biomaterials with well-defined architectures and tunable properties for emerging biomedical applications. Click chemistry, a powerful method allowing specific and controllable bioorthogonal reactions, has revolutionized our ability to make complex molecular structures with a high level of specificity, selectivity, and yield under mild conditions. These features combined with minimal byproduct formation have enabled the design of a wide range of macromolecular architectures from quick and versatile click reactions. Furthermore, copper-free click chemistry has resulted in a change of paradigm, allowing researchers to perform highly selective chemical reactions in biological environments to further understand the structure and function of cells. In living systems, introducing clickable groups into biomolecules such as polysaccharides (PSA) has been explored as a general approach to conduct medicinal chemistry and potentially help solve healthcare needs. De novo biosynthetic pathways for chemical synthesis have also been exploited and optimized to perform PSA-based bioconjugation inside living cells without interfering with their native processes or functions. This strategy obviates the need for laborious and costly chemical reactions which normally require extensive and time-consuming purification steps. Using these approaches, various PSA-based macromolecules have been manufactured as building blocks for the design of novel biomaterials. Clickable PSA provide a powerful and versatile toolbox for biomaterials scientists and will increasingly play a crucial role in the biomedical field. Specifically, bioclick reactions with PSA have been leveraged for the design of advanced drug delivery systems and minimally invasive injectable hydrogels. In this review article, we have outlined the key aspects and breadth of PSA-derived bioclick reactions as a powerful and versatile toolbox to design advanced polymeric biomaterials for biomedical applications such as molecular imaging, drug delivery, and tissue engineering. Additionally, we have also discussed the past achievements, present developments, and recent trends of clickable PSA-based biomaterials such as three dimensional printing, as well as their challenges, clinical translatability, and future perspectives. Graphical abstract: Image, graphical abstract